Development of methods for standardization of the active substance, namely the model mixture based on decamethoxine and thiotriazoline - Kucherenko, L. I.; Chonka, O. O.; Portna, O. O.; Кучеренко, Людмила Іванівна; Чонка, Олена Олегівна; Портна, Олена Олексіївна; Кучеренко, Л. И.; Чонка, Е. О.; Портная, Е. А. (Запорізький державний медичний університет, 2021)
Today, the important problem is the creation of new decamethoxine and thiotriazoline based drugs for the treatment of stomatitis. The aim of the work is to develop a method for quantitative determination of decamethoxine and thiotriazoline in the model mixture (1:25) by spectrophotometry. Materials and methods. Series 6 model mixtures were made at the ratio of decamethoxine and thiotriazoline 1:25. We used certified substances: thiotriazoline series GTT 3460911 (manufacturer: State Enterprise Chemical Reagents Plant, Kharkiv), decamethoxine series № 010915 (manufacturer: LLC “PHARMCHIM”). Optizen POP spectrophotometer, polyvinyl alcohol, hydrochloric acid, and eosin were used. Results. A method for quantitative determination of decamethoxine and thiotriazoline in MS was developed. It was established that the content of active substances in MS is thiotriazoline from 0.5021 to 0.5096, decamethoxine from 0.0207 to 0.0211. Conclusions. A method for quantitative determination of decamethoxine and thiotriazoline in MS has been developed. The method of quantitative determination of decamethoxine and thiotriazoline in MS is reproducible. Створення нових лікарських засобів для лікування стоматиту на основі декаметоксину та тіотріазоліну – актуальна проблема. Мета роботи – розроблення методики кількісного визначення декаметоксину та тіотріазоліну в модельній суміші (1:25) методом спектрофотометрії. Матеріали та методи. Використали 6 серій модельних сумішей (МС), тіотріазолін серії GTT 3460911 (виробник – ДП «Завод хімічних реактивів» НТК ІМК НАН УКРАЇНИ», м. Харків), декаметоксин серії № 010915 (виробник – ТОВ «ФАРМХІМ», м. Шостка). Дослідження виконали, застосувавши спектрофотометр Optizen POP, полівініловий спирт, соляну кислоту, еозин. Результати. Розробили методику кількісного визначення декаметоксину та тіотріазоліну в модельній суміші. Встановили, що вміст діючих речовин у МС становить: тіотріазоліну – 0,5021–0,5096, декаметоксину – 0,0207–0,0211. Висновки. Розроблено методику кількісного визначення декаметоксину та тіотріазоліну в МС. Метод кількісного визначення декаметоксину та тіотріазоліну в модельній суміші є відтворюваним. Создание новых лекарственных средств для лечения стоматита на основе декаметоксина и тиотриазолина – актуальная проблема. Цель работы – разработка методики количественного определения декаметоксина и тиотриазолина в модельной смеси (1:25) методом спектрофотометрии. Материалы и методы. Использовали 6 серий модельных смесей (МС) тиотриазолина серии ГТТ 3460911 (производитель – ГП «Завод химических реактивов» НТК ИМК НАН Украины, г. Харьков), декаметоксин серии № 010915 (производитель – ООО «ФАРМХИМ», г. Шостка). В ходе исследования применили спектрофотометр Optizen POP, поливиниловый спирт, соляную кислоту, эозин. Результаты. Разработали методику количественного определения декаметоксина и тиотриазолина в МС. Установлено, что содержание действующих веществ в модельной смеси составляет: тиотриазолина – 0,5021–0,5096, декаметоксина – 0,0207–0,0211. Выводы. Разработана методика количественного определения декаметоксина и тиотриазолина в МС. Метод количественного определения декаметоксина и тиотриазолина в модельной смеси воспроизводим.
Розроблення методики стандартизації діючих речовин у модельній суміші на основі декаметоксину та тіотріазоліну
Разработка методики стандартизации действующих веществ в модельной смеси на основе декаметоксина и тиотриазолина
Кучеренко Л. І. - ORCID ID: 0000-0003-2229-0232; Чонка О. О. - ORCID ID: 0000-0002-6793-2668; Портна О. О. - ORCID ID: 0000-0002-4752-1888.
Keywords: decamethoxine; thiotriazoline; model mixtures; spectrophotometry; декаметоксин; тіотріазолін; модельні суміші; спектрофотометрія; декаметоксин; тиотриазолин; модельные смеси; спектрофотометрия